2010
DOI: 10.1016/j.juro.2010.02.1246
|View full text |Cite
|
Sign up to set email alerts
|

1508 Tanezumab Reduces Pain and Urgency in Interstitial Cystitis: Results of a Phase 2 Trial

Abstract: METHODS: A total of 599 women with diagnoses of interstitial cystitis/painful bladder syndrome (IC/PBS) and/or endometriosis, vulvodynia, or overactive bladder (OAB) were recruited from the clinical practices of urologists (nϭ8) and gynecologists (nϭ15) across the United States and interviewed by telephone. Subjects who reported pain, pressure or discomfort in the lower abdomen or pelvic area were asked to describe exactly what these sensations felt like. Responses were recorded verbatim, coded and analyzed. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After 6 weeks, a single 250 µg/kg i.v. injection of tanezumab reduced average self‐reported daily pain score and urgency episode frequency, but had no effect on micturition frequency or mean voiding volume 150. However, currently, further studies in IC/PBS have been suspended in conjunction with serious adverse events observed with tanezumab in trials with ostheoarthritis patients (http://clinicaltrials.gov/).…”
Section: Ngf In Bladder Dysfunctionmentioning
confidence: 99%
“…After 6 weeks, a single 250 µg/kg i.v. injection of tanezumab reduced average self‐reported daily pain score and urgency episode frequency, but had no effect on micturition frequency or mean voiding volume 150. However, currently, further studies in IC/PBS have been suspended in conjunction with serious adverse events observed with tanezumab in trials with ostheoarthritis patients (http://clinicaltrials.gov/).…”
Section: Ngf In Bladder Dysfunctionmentioning
confidence: 99%